(untitled) (Quest Journal of Management and Social Sciences, 2022)
Background: The election is a process of transferring power and authorities to lead the public position in democratic practice. This process not only hands over the power for the decision making but also introduces changes in the governing system that influence either way to the individual, firms, community, society, and the entire nation through various governing tools. An election affects the economic system from within and outside in south-Asian countries. Therefore, the south-Asian economy keeps tracking the different types of elections to adjust their economic system accordingly grounded on the level of its harm and benefits. Academic research can provide a directional understanding of how the election can influence the economy. Objective: The major objective of this study is to examine the impact of the national election on the economy in South Asian countries. Methods: This study has employed the panel data of five major south-Asian countries: Bangladesh, India, Nepal, Pakistan, and Sri Lanka, from 1960 to 2020. We collected the series of data from the World Bank database and the official websites of respective countries. The data were empirically analyzed using the difference-in-difference (DID) method and descriptive statistics. Results: An empirical analysis result shows a positive role of the national election in South Asia except for Pakistan. Further, this study also indicates that the coefficient of different-in-difference is positive, indicating a positive impact of the first Constituent Assembly Election-2008 on economic growth in Nepal. However, this analysis also shows that the national election before the Constituent Assembly (CA) Election-2008 had a more significant positive impact on economic growth than the post-CA elections in Nepal. Conclusions: Overall, this study concludes that the national election has a positive impact on economic growth in South Asia except for Pakistan, but the degree of influence depends on the socio-political and economic structure of the respective country in the region. Implications: The findings of this paper would be useful for scholars interested in a sociopolitical economy in the south Asian region and equally valuable for the policy stakeholders.